Fecal microbiome transplant from patients with lactation mastitis promotes mastitis in conventional lactating mice - Kong, Chao-Yue; Yang, Yi-Qin; Han, Bing; Chen, Hui-Ling; Mao, Yu-Qin; Huang, Jia-Ting; Wang, Li-Shun; Li, Zhan-Ming (Frontiers in Microbiology, 2023)
Introduction Lactation mastitis seriously severely affects the health of lactating females and their infants, yet the underlying causes of clinical lactation mastitis remain unclear. Methods In this study, we used microbiota-humanized mice as a model to investigate the role of gut microbiota in lactation mastitis. We compared the fecal microbiota of lactation mastitis patients and healthy individuals and conducted fecal microbiota transplantation (FMT) experiments in an antibiotic-pretreated mouse model to test whether gut microbes contribute to human lactation mastitis. Results Our results showed that gut microbiota diversity was reduced and dysbiosis was present in lactating mastitis patients. FMT from lactation mastitis patients (M-FMT), but not from healthy individuals (H-FMT), to antibiotic-treated mice resulted in lactation mastitis. The inflammation in mice caused by gut microbiota from lactating mastitis patients appears to be pervasive, as hepatocytes from mice that received feces from lactating mastitis patients showed marked swelling. In addition, serum pro-inflammatory factors, including IL-4, IL-17, MPO, IL-6, IL-1β, and TNF-α, were significantly increased in the M-FMT group. The Firmicutes/Bacteroidetes ratio (F/B), a biomarker of gut dysbiosis, was significantly increased in the M-FMT group. At the phylum level, Actinobacteria were significantly increased, and Verrucomicrobia were significantly decreased in the M-FMT group. At the genus level, Ruminococcus and Faecalibacterium were significantly reduced, while Parabacteroides were significantly increased in the feces of both patients with lactation mastitis and M-FMT mice. Moreover, our study revealed an “amplification effect” on microbiota differences and mastitis disease following human-to-mouse FMT. Conclusion Collectively, our findings demonstrate that the gut microbiota in lactating mastitis patients is dysbiotic and contributes to the pathogenesis of mastitis.